Evolution of US public diplomacy: Domestic political determinants, priorities and new challenges - P. А. Sharikov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Public diplomacy remains one of the most dynamic and important areas of the modern US foreign policy. As such, the US public diplomacy, — its institutional structure, principles of functioning, key priorities, etc. — attracts increasing attention within both Russian and foreign academic literature. However, for a more complete understanding of the contemporary US public diplomacy specifics and prospects, it seems appropriate to try to fit it into a broader context of the evolution of the US political system in general. The first section of the paper identifies the major domestic political factors that determined the development of the US foreign policy mechanism, as well as the key stages of its evolution. The author argues that one of the key trends in the almost 250-year history of the American political system development was its gradual democratization, aimed to promote inclusion of a larger section of population in political processes. The second section examines the role of public diplomacy within the framework of the contemporary US foreign policy. The author notes that the latest developments in information and communication technologies have turned publicity and PR-campaigns into the most important factors of domestic political competition in the United States in the 21st century. The Internet and social networks have opened up virtually unlimited opportunities for political campaigning both inside and outside the state, giving a new impetus to the development of the US public diplomacy. At the same time, digital technologies have also generated new challenges, raising the problem of ensuring information security in the face of expansion of social networks. In this regard, the third section touches upon the issues of evaluating the effectiveness of the US public diplomacy. The author concludes that in terms of possible directions for further research the interactions between the United States and the EU countries which share common values are of particular importance. This may allow for a better understanding of the possibilities and limits of the US public diplomacy tools based on the institutions of a developed civil society.